Law Enforcement Transnational Crimes against State Security and Sovereignty in the VUCA Era (Universitas Terbuka, 2023)
Transnational crime, or commonly known as transnational crime, can cause a lot of harm to a country, even to certain areas within the country. There are many forms of deviation that can be done, such as overexploitation of natural and human resources that have an impact on global society. Problems such as poverty and conflict are often triggers for transnational crime. With its ability to cross national borders and impact other countries, transnational crime poses a serious threat to global security. The establishment of legal policy must begin by determining acts as criminal offenses and establishing sanctions for perpetrators of crimes (criminalization). Transnational criminal acts can be identified in legal provisions by grouping the elements of unlawful acts that can be subject to criminal sanctions. Law enforcement is carried out based on the area where transnational crime occurs.